(untitled) (Research, Society and Development, 2021)
Objective: To identify the difficulties of mothers hospitalized in a maternity hospital in the interior of Sergipe in breastfeeding their first child. Methods: For quantitative analysis, frequency distributions were performed using the Statistical Package for the Social Sciences for Windows- SPSS version 21 program. Result: It was found that all claimed to have been guided about the benefits of breastfeeding and about the 10 steps to promote breastfeeding, as well as 31 (50%) stated that they thought breastfeeding was good and 31 (50%) reported that breastfeeding was excellent. It is noteworthy that all newborns of the mothers in the study remained in rooming-in during the entire hospital stay. Conclusion: The results point to a satisfactory result in relation to Exclusive Breastfeeding and its difficulties during the study period, and it became evident that the study setting provides prior guidance to mothers in relation to the breastfeeding process. Adequate guidance of mothers about breastfeeding is important for successful breastfeeding in the postpartum period, alleviating possible problems such as pain during breastfeeding and early weaning.